DETERMINATION OF GRANULATED SUGAR ALTERNATIVES USING ANALYTICAL HIERARCHICAL PROCESS (AHP) - Mastrisiswadi, Hasan; Solihin, Kurniaji Wahid; Azis, Ardiyanto; Robbiyamto, Nurul Hidayat (J@ti Undip : Jurnal Teknik Industri, 2020)
In 2019, the government planned to achieve sugar self-sufficiency to meet domestic sugar needs. One type of sugar that is most consumed is granulated sugar. In Indonesia, various models, prices, and sizes of sugar are marketed. Competition for producers in selling their products is getting tighter, so they need to understand the criteria that influence consumers in buying granulated sugar. Research on sugar has been conducted, but until now, research on determining the criteria for sugar products has never been conducted. Many factors are the criteria for choosing sugar to be selected by consumers. To find out what alternatives and criteria are preferred by consumers, the method of Analytical Hierarchical Process (AHP) is used. AHP method consists of several stages that are: hierarchy determination, evaluation of criteria and alternatives, Synthesis of priority, logical consistency, and preference value. From the results of calculations that carried out, it was found that the quality and taste were the highest criteria as a reference for choosing sugar brands.